Assessment of cognitive instrumental activities of daily living: a systematic review. Issue 10 (8th May 2021) - Romero-Ayuso, Dulce; Castillero-Perea, Álvaro; González, Pascual; Navarro, Elena; Molina-Massó, José Pascual; Funes, M. Jesús; Ariza-Vega, Patrocinio; Toledano-González, Abel; Triviño-Juárez, José Matías
Abstract: Purpose: Cognitive instrumental activities of daily living are particularly related to executive functions, such as scheduling appointments, monthly payments, managing the household economy, shopping or taking the bus. The aim of this systematic review was to determine the available tests for the assessment of executive functions with ecological validity to predict individuals' functioning. Materials and methods: An electronic search was conducted in MEDLINE, Cochrane Central, PsyCInfo and IEEE Xplore until May 2019, in addition to a manual search. The PRISMA criteria and the Covidence platform were used to select articles and extract data. Results: After applying the search selection criteria, 76 studies were identified. They referred to 110 tools to assess instrumental activities of daily living. Those that have received most attention are related to menu preparation and shopping. Performance-based measures are the most widely used traditional methods. Most tests were aimed at the adult population with acquired brain damage, cognitive impairment or dementia. There was a predominance of tests based on the Multiple Errands Test paradigm. Conclusions: In recent years, it has increased the number of tools that assess the instrumental activities of daily living based on technologies such as personal or environmental sensors and serious games. IMPLICATIONS FOR REHABILITATION: Assessment of Instrumental Activities of Daily Living through performance-based measures is especially useful for the early detection of dysfunctions or preclinical disability. Difficulties in performing instrumental activities of daily living are closely associated with deficits in executive functions and prospective memory. Activities of Daily Living can be understood as multitasks. The use of virtual reality-based tests was shown to be sensitive to the detection of cognitive deficits in Activities of Daily Living. An advantage of using virtual reality in assessments is that it can help to predict the level of personal autonomy in patients who are in an institutional environment and could be a first approximation to the real environment.